Emerging market business cycles revisited: learning about the trend - Emine Boz; Christian Daude; C. Bora Durdu (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
We build an equilibrium business cycle model in which agents cannot perfectly distinguish between the permanent and transitory components of TFP shocks and learn about those components using the Kalman filter. Calibrated to Mexico, the model predicts a higher variability of consumption relative to output and a strongly negative correlation between the trade balance and output for a wide range of variability and persistence of permanent shocks vis-a-vis the transitory shocks. Moreover, our estimation for Mexico and Canada suggests more severe informational frictions in emerging markets than in developed economies.
Keywords: F41; E44; D82; 330; emerging markets; business cycles; learning; Kalman filter; Konjunktur; Schwellenländer; Produktivität; Zustandsraummodell; Zeitreihenanalyse; Schätzung; Mexiko; Kanada